So true a love - Barker, Joanna L., 1990- (Proper romance., 2024)
"Verity Travers, a well-connected lady and private investigator, retires after a perilous case. However, a personal attack on her friend reignites her determination to catch the assailant. Verity is forced to team up with the dashing Bow Street Runner Nathaniel Denning, and as they close in on the truth, their investigation becomes more complicated than ever as danger and passion collide"--